2016
DOI: 10.3109/09273948.2016.1139734
|View full text |Cite
|
Sign up to set email alerts
|

Visual Functioning and Health-related Quality-of-Life are Compromised in Patients with Uveitis

Abstract: Patients with uveitis have significantly poorer VR- and HR-QoL than healthy control subjects. Uveitis has a more debilitating impact on VR-QoL than DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
0
16
1
13
Order By: Relevance
“…79 Previous studies have demonstrated that patients with uveitis have a lower quality of life compared to the general population 7,1013 and, in some cases, a lower quality of life compared to patients with other eye conditions. 14,15 Studies on quality of life in patients with noninfectious uveitis requiring systemic immunosuppressant therapy, however, have been limited in number and have typically explored populations on heterogeneous medication regimens.…”
Section: Introductionmentioning
confidence: 99%
“…79 Previous studies have demonstrated that patients with uveitis have a lower quality of life compared to the general population 7,1013 and, in some cases, a lower quality of life compared to patients with other eye conditions. 14,15 Studies on quality of life in patients with noninfectious uveitis requiring systemic immunosuppressant therapy, however, have been limited in number and have typically explored populations on heterogeneous medication regimens.…”
Section: Introductionmentioning
confidence: 99%
“…21 Several studies have focused on the effect of uveitis symptoms on quality-of-life outcomes. [22][23][24][25][26][27] Given that both uveitis and corticosteroid therapy are related to an increased likelihood of complications, it may be difficult to determine disease vs treatment effect on comorbidity and quality of life. Moreover, noninfectious uveitis is associated with a number of systemic disorders, including Behçet disease, juvenile idiopathic arthritis, rheumatoid arthritis, Vogt-Koyanagi-Harada disease, sarcoidosis, ankylosing spondylitis, psoriatic arthritis, and multiple sclerosis.…”
mentioning
confidence: 99%
“…20,29,35,41,48,49,55 Other indications for the use of NCSIT may include disease that severely impairs essential activities of daily living and, consequently, quality of life. 59,60 Contraindications to corticosteroid therapy include behavioral patterns (noncompliance), health-related factors (e.g., history of tuberculosis or hepatitis), and reproductive status (Appendix 6, available at www.aaojournal.org). It should be noted that these contraindications should be evaluated within the context of the overall benefit versus the risk of any therapy.…”
Section: Resultsmentioning
confidence: 99%